Co-expression Mechanism Analysis of Different Tachyplesin I–Resistant Strains in Pseudomonas aeruginosa Based on Transcriptome Sequencing - Hong, Jun; Li, Xinyang; Jiang, Mengyao; Hong, Ruofei (Frontiers in Microbiology, 2022)
Tachyplesin I is a cationic antimicrobial peptide with 17 amino acids. The long-term continuous exposure to increased concentrations of tachyplesin I induced resistance in Pseudomonas aeruginosa. The global gene expression profiling of tachyplesin I–resistant P. aeruginosa strains PA-60 and PA-99 and the sensitive strain P. aeruginosa CGMCC1.2620 (PA1.2620) were conducted by transcriptome sequencing to analyze the common underlying mechanism of resistance to tachyplesin I in low- or high-resistance mutants. The co-expression patterns, gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment, sRNA target genes, and single-nucleotide polymorphism (SNP) change were analyzed for the co-expressed genes in this study. A total of 661 differentially co-expressed genes under treatments of PA1.2620 versus PA-99 and PA1.2620 versus PA-60 (HL) were divided into 12 kinds of expression patterns. GO and KEGG pathway enrichment analyses indicated that the enrichment of co-expressed genes was mainly associated with oxidoreductase activity, mismatched DNA binding, mismatch repair, RNA degradation of GO terms, aminoacyl-tRNA biosynthesis, and aminobenzoate degradation pathways, and so forth. The co-expressed resistance-related genes were mainly involved in antibiotic efflux and antibiotic inactivation. Seven co-expressed genes had SNP changes. Some co-expressed sRNAs were involved in P. aeruginosa resistance to tachyplesin I by regulating target genes and pathways related to resistance. The common resistance mechanism of P. aeruginosa among different mutants to tachyplesin I was mainly associated with the expression alteration of several genes and sRNA-regulated target genes related to resistance; few genes had base mutations. The findings of this study might provide guidance for understanding the resistance mechanism of P. aeruginosa to tachyplesin I.